PENANAMAN NILAI-NILAI PANCASILA DALAM PEMBENTUKAN MORAL DAN KARAKTER ANAK USIA DINI MELALUI PEMBELAJARAN DI PAUD - Firyal Lubna Annaisha; Zahrah Najwa Farida; Dewi Juliasih; Zaenul Slam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the instillation of Pancasila values in the moral and character development of young children through early childhood education. This study employs a literature review method by analyzing various recent scientific literature related to Pancasila values, character education, and early childhood education. The findings indicate that Pancasila values can be instilled through habit formation, teacher modeling, storytelling, educational games, project-based learning, thematic activities, and learning based on local culture. These strategies support the development of religiosity, tolerance, mutual cooperation, honesty, responsibility, independence, social concern, and simple deliberation. However, their implementation still faces challenges in the form of varying teacher interpretations, limited learning resources, and suboptimal collaboration among schools, families, and the community. This study concludes that Pancasila-based learning in early childhood education (PAUD) must be designed in a structured, contextual, sustainable, and developmentally appropriate manner to ensure that Pancasila values are reflected in childrens daily moral behavior.